“Tudo é vaidade e correr atrás do vento”: as figuras retóricas na construção da argumentação no livro de Eclesiastes - Prado, Márcia Andreia Granero (2017)
In this research, we intend to examine how figures of rhetoric are organized in the construction of Coélet's argument in the Book of Ecclesiastes based on the hypothesis that the discourse manifested in the Prologue and Chapter 1 of this book uses figures as a rhetorical device to guarantee adhesion from the audience to the message the author wants to convey. Thus, the corpus of our research consists in the Prologue and in Chapter I of the Book of Ecclesiastes, which integrates the Old Testament of the Judeo-Christian Bible. The choice of a biblical text is based on the fact that the Bible is one of the oldest books of the Western world and marks the history of humankind, not to mention that it is the most published book worldwide. In the Bible, the Book of Ecclesiastes is a text whose speaker argues about the human being's attempt to find meaning in the world in which they live. For the analysis, we will adopt the rhetoricargumentative theory with respect to the concepts systematized by Aristotle and disseminated and amplified by the contemporary authors Perelman and Olbrechts-Tyteca, Michel Meyer, and Olivier Reboul, among others. We will also seek support on the work of linguists such as José Luiz Fiorin, especially with regard to the study of rhetorical figures. By examining the articulation of figures on the basis of a rethorical tripod and by analyzing how the argumentative process stages engender speakers Coélet’s speech, we identify some rethorical figures that the speaker uses in each parto of the argumentative process as he evokes ethos, pathos, and logos. Finally, we also observe which rethorical figures conduct the reader from one stage to the other.